CUTANEOUS LEISHMANIASIS: AN EMERGING CHILDHOOD INFECTION - Shoaib, Shaheen; Tauheed, Shoaib; Hafeez, Amtul (Journal of Ayub Medical College Abbottabad, 2007)
Background: Cutaneous Leishmaniasis (CL) has been an endemic parasitic infection in certain areas of Pakistan. New outbreaks have occurred in many areas not identified previously especially in the province of Sindh. The object of this study was to see the prevalence of CL as a childhood disease. Methods: It was a cross sectional study in which 400 cases coming to various skin disease clinics were included for confirmation of CL by microscopy, culture and PCR. Results: Out of 400 cases, 185 cases of ages from 1-14 years were diagnosed clinically and confirmed by Lab. Tests for CL. Both dry and wet types of lesions were observed that indicated presence of more than one strain of the parasite. Conclusion: Cutaneous Leishmaniasis was found to be significantly prevalent in children. The strains were found to be L. tropica and L. major as was indicated by the nature of lesions and confirmed by PCR. Keywords: Cutaneous leishmaniasis, Childhood infection, L. tropica, L. major.